On the taxonomic status of the tenebrionoid genera Falsopedilus Pic, 1924 and Hintonosia Báguena Corella, 1948 (Coleoptera: Mycteridae) with descriptions of new species - Gompel, Nicolas; Telnov, Dmitry (Zootaxa, 2023)
We re-evaluate the taxonomic placement of the genus Hintonosia Báguena Corella, 1948, hitherto placed in Aderidae Csíki, 1909. The assessment of key morphological characters based on the type specimen of the type species of this genus, Hintonosia bismacrocephalus Báguena Corella, 1948 (= Hintonosia macrocephalus Pic, 1935, homonym), demonstrated that it does not possess the synapomorphies of the Aderidae. Instead, its clear position in Mycteridae Blanchard, 1845 is uncovered, leading us to the transfer of Hintonosia to the subfamily Eurypinae Thomson, 1860 of Mycteridae. Moreover, Hintonosia was found congeneric with the mycterid genus Falsopedilus Pic, 1924 and the new synonymy is therefore proposed. Additionally, two African species of Falsopedilus are described, a key to, and a checklist of Falsopedilus species are presented.